APPLICATIONS BREATHING DISORDERS TREATMENT WITH PLANT MEDICINES USING VISUAL BASIC 6.0. - Nano Handoko (Jurnal Sistem Informasi, 2006)
Any disruption or disease have different treatment in both the treatment penyembuhanya chemical or medicinal plants, as well as respiratory problems which can be treated by using vegetable or plant wealth efficacious drugs. To help cure the problem then the author tries to make the application Respiratory Disorder Treatment With Medicinal Plants Using Visual Basic 6.0.Application discussion respiratory treatment with medicinal plants is divided into four stages namely, making flowcharts, menu structure, design input and output, and manufacturing programs with Visual Basic 6.0.